Assessing soil erosion hotspots and land degradation extent in Beshilo Watershed, Northeastern Ethiopia: integrating geospatial and field survey techniques, for sustainable land management - Workie, Melak Desta; Teku, Degfie (Frontiers in Environmental Science, 2025)
IntroductionSoil erosion and land degradation pose significant threats to sustainable resource management in the Beshilo Watershed, Northeastern Ethiopia. These challenges are driven by steep slopes, unsustainable agricultural practices, and deteriorating soil health, necessitating a comprehensive assessment to inform effective mitigation strategies.Methods This study integrates geospatial analysis and field surveys to evaluate land degradation severity and identify soil erosion hotspots. The Revised Universal Soil Loss Equation (RUSLE) model, land use/land cover (LULC) analysis, and normalized difference vegetation index (NDVI) mapping are employed alongside FAO soil data, including soil organic matter (SOM), texture, and permeability assessments. GPS-documented inventories of active landslides and gullies further enhance the analysis.ResultsThe findings reveal alarming soil erosion rates, with RUSLE values ranging from 0 to 1,288 t/ha/year, an average annual loss of 68.3 t/ha/year, and a total soil loss of 664,333 tonnes‐far exceeding Ethiopia’s tolerable limits of 12‐18 t/ha/year. Approximately 38.5% of the watershed is categorized as high or severe erosion risk. GIS analysis reports a standard deviation of 100.06 for soil loss, highlighting spatial variability. LULC analysis shows that 73.4% of the area is under cultivation, while forest cover has declined to 7%. NDVI values range from ‐0.24 to 0.58, indicating severe vegetation degradation. Soil assessments report low SOM levels (1‐3%), weak soil structure ratings (1‐4), and a predominance of sandy loam texture (78%), all contributing to heightened erosion vulnerability.Discussion and ConclusionThe results highlight the urgent need for targeted Sustainable Land Management (SLM) interventions to mitigate soil erosion and rehabilitate degraded lands. Recommended measures include terracing, agroforestry, vegetative buffer strips, and integrated soil and water conservation strategies. These findings provide essential data to support evidence-based policymaking and the implementation of effective land management practices in erosion-prone regions.